Trends in the method and gestational age of abortion in high-income countries. Issue 2 (8th April 2019) - Popinchalk, Anna; Sedgh, Gilda
Abstract : Background: Examining the distribution of abortions by method of abortion and gestational age at time of termination provides insight about the options women may have to terminate their pregnancies. Comparing these distributions across countries and over time is an important step toward understanding the factors that can drive these distributions, including regulations and practices related to the provision of abortion services, and women's preferences and needs. Methods: We sought official statistics on gestational age and method of abortion for all high-income countries with liberal abortion laws. For the 24 high-income countries with available data, we calculated percentage distributions of abortions by gestational age of pregnancy and method of abortion for 2017 or the most recent year for which data were available, and assessed trends in the preceding 10 years whenever possible. Results: Medication (or medical) abortion accounts for at least half of all abortions in the majority of countries. In the majority of countries over 90% of all abortions were completed before 13 weeks, and more than two-thirds of abortions occurred before the first 9 weeks of gestation. Over the past 10 years there has been an increase in both the proportion of abortions that were medication abortions and the proportion that were obtained before 9 weeks gestation. Conclusions: These findings highlight changes in abortion provision in the past decade. More research is needed to understand whether the observed distributions are a function of women's preferences or of barriers to the timing and type of care they would prefer.